2019
DOI: 10.1111/bjhp.12402
|View full text |Cite
|
Sign up to set email alerts
|

Social cognitions and smoking behaviour: Temporal resolution matters

Abstract: Objectives. Health behaviour theories outline how cognitions predict behaviours, but rarely specify the temporal relation between cognitions and behaviours. It is not known whether these predictive relationships vary depending on temporal resolution or whether the relative influence of cognitions varies with measurement schedules.The current exploratory study therefore investigates whether the associations between behavioural cognitions (self-efficacy, intention, and risk perception) and smoking vary when meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…The present research helps to understand why previous studies on the association between risk perceptions and behaviour during the COVID-19 lockdown have not been unanimous up to this point [ 51 56 ]. Whilst health related risks positively correlated with compliant behaviour, other risk perceptions such as economic and liberty risks negatively correlated with the likelihood of following government guidelines.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The present research helps to understand why previous studies on the association between risk perceptions and behaviour during the COVID-19 lockdown have not been unanimous up to this point [ 51 56 ]. Whilst health related risks positively correlated with compliant behaviour, other risk perceptions such as economic and liberty risks negatively correlated with the likelihood of following government guidelines.…”
Section: Discussionmentioning
confidence: 85%
“…However, mixed findings have also been reported. One set of studies demonstrated a strong interaction between risk perceptions and actions in opposition to general protective behaviours (such as with respect to cycling) [51][52][53], while another found no relationship between risk perception and general protective behaviour [54][55][56]. The theory of risk aversion demonstrates how people will act irrationally in order to escape perceived risks, regardless of whether those risks are present or objectively salient [57,58].…”
Section: Risk Perceptionsmentioning
confidence: 99%
“…That is, on time points when self-monitoring was higher-than-usual, no significant elevated levels of subsequent hand washing were found. Prediction strength of within-level associations is not always superior to between-level associations of the same constructs [ 37 ]. Recent methodological articles focusing on this phenomenon concluded that the temporal resolution matters [ 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prediction strength of within-level associations is not always superior to between-level associations of the same constructs [ 37 ]. Recent methodological articles focusing on this phenomenon concluded that the temporal resolution matters [ 35 , 37 ]. As within-person effects are referring to lagged analyses in the present study, issues of shared method variance of same-time analyses are circumvented [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no research examining associations between maternal self-efficacy and alcohol use. In addition, no study to date has examined daily or momentary changes in maternal self-efficacy during the postpartum period despite evidence that self-efficacy in other domains changes over brief periods [ 59 , 79 , 80 ]. This study will explore the associations between maternal self-efficacy and drinking at the daily and momentary levels to inform whether maternal self-efficacy may be an important intervention target for new mothers who engage in risky drinking.…”
Section: Methodsmentioning
confidence: 99%